The Role of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Company Size on Profitability - Nuramal Nuramal; Asbi Amin; Sitti Mispa (Al-Buhuts, 2024)
The aim of this research is to determine the influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and company size on the profitability of banks listed on the Indonesia Stock Exchange for the 2019-2023 period. The population of this research is banking companies listed on the Indonesian Stock Exchange within the research period (2019 to 2023). as many as 42 banks. Sampling used purposive sampling. Based on these sample criteria, the number of samples that meet the criteria for use in this research is 50 financial reports from 10 companies listed on the Indonesia Stock Exchange for the period 2019 to 2023. The econometric model used is a panel data regression analysis model using Eviews 12 The research results found that the Capital Adequacy Ratio (CAR) had a positive and significant effect on profitability, while the Loan to Deposit Ratio (LDR) and company size did not have a positive and significant effect on profitability.